L’option européenne du Canada dans les années 80 - Pentland, Charles (Études internationales, 1983)
The year 1982 marked the twenty-fifth anniversary of the Treaty of Rome, creating the EEC, and the tenth anniversary of Canada s Third Option, which aimed in part at using the new Europe as a counterweight to American influence. This article attempts, first to set the last ten year s of Canada s European policy in the context of postwar economic and strategic relationships and, secondly, to evaluate the European aspect of the Third Option and its prospects for the 1980s.Canada s image of, and policy towards, Western Europe, has always had two distinct elements — economic and strategic - whose interplay describes various phases of the relationship. Until about 1957, the two images were roughly congruent and Canada s economic and military policies mutually reinforcing. A multilateral Atlantic economic community was seen as the underpinning of collective defence. The next fifteen years or so saw the breakup of this patte m, with the emergence of the Community, continued British attempts to join from 1961 on, and the decline in Canadian support for NATO.The birth of the Third Option and the pursuit of the Framework Agreement with the Community saw the gradual revival of Canada's military relationship with Europe, this time in the service of economic diversification and growth. A variety of factors, however - global, European, North American and domestic Canadian - hampered the development of the new link with the Community. Many of these, especially the structural ones underlying the crisis of the world economy and the stagnation of European integration - are likely to persist through the 1980 s. For the next few year s, then, the European option will probably be (a) less communautaire, (b) a less important focus in trade policy relative to other areas, and (c) once more in the service of military and political ends.